2019
DOI: 10.1177/0907568219881667
|View full text |Cite
|
Sign up to set email alerts
|

Senses of belonging when living in foster care families: Insights from children’s video diaries

Abstract: This article explores how children living in foster care create senses of belonging across diverse family relationships. It draws on video diaries made by 11 Danish children living in foster care. For the analysis, we have selected two video diaries, made by two girls, aged 12 and 15 years, who live in foster care and have regular contact with their birth family. The girls differ in their senses of belonging but both reflectively negotiate this across their family relationships creating more or less emotional,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Instead it is how we ascribe meaning to, interpret and enact family relationships that dynamically form our notion of family (Morgan, 2011). Research has shown that children in care actively do family relationships across family settings and their relationships with for instance foster carers depend on the meanings they ascribe hereto (Bengtsson & Luckow, in press; Biehal, 2014; Boddy, 2018). When this article engages with talking about ‘foster care families’ and the relationships in this setting as ‘family relationships’, it is not to disregard how ‘family relationships’ very much depend on the quality and the meaning that are ascribed to them.…”
Section: Everyday Practices In Foster Care Familiesmentioning
confidence: 99%
“…Instead it is how we ascribe meaning to, interpret and enact family relationships that dynamically form our notion of family (Morgan, 2011). Research has shown that children in care actively do family relationships across family settings and their relationships with for instance foster carers depend on the meanings they ascribe hereto (Bengtsson & Luckow, in press; Biehal, 2014; Boddy, 2018). When this article engages with talking about ‘foster care families’ and the relationships in this setting as ‘family relationships’, it is not to disregard how ‘family relationships’ very much depend on the quality and the meaning that are ascribed to them.…”
Section: Everyday Practices In Foster Care Familiesmentioning
confidence: 99%
“…Although both non-kinship foster care and kinship foster care have been found to provide secure and stable homes (Biehal, 2019), many children also experience instability (Hedin, 2014) and uncertainty (Biehal, 2012, p. 959). Bengtsson and Luckow (2020) examined in their study 'how children living in foster care create senses of belonging ' (p. 106). According to them, the child must not just find its place in the new family, but also navigate between 'new and old family relations' (Bengtsson & Luckow, 2020, p. 107), which 'is not accomplished once and for all but is an ongoing process of feeling at home and being recognized as a rightful member of diverse family settings' (Bengtsson & Luckow, 2020, p. 116).…”
Section: Introductionmentioning
confidence: 99%
“…Bengtsson and Luckow (2020) examined in their study ‘how children living in foster care create senses of belonging’ (p. 106). According to them, the child must not just find its place in the new family, but also navigate between ‘new and old family relations’ (Bengtsson & Luckow, 2020, p. 107), which ‘is not accomplished once and for all but is an ongoing process of feeling at home and being recognized as a rightful member of diverse family settings’ (Bengtsson & Luckow, 2020, p. 116).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on the social relationships involved in foster care has tended to focus on children living in foster care and their perception of their dual family relationships (Bengtsson and Luckow, 2019; Biehal, 2014; Christiansen et al, 2013; Holland and Crowley, 2013; Pithouse and Rees, 2015; Sen and Broadhurst, 2011; Sinclair et al, 2000). Among many other findings, this research describes the importance of contact between children in foster care and their birth parents, also showing how the frequency and regularity of contacts, and professional support for these contacts, affect how the relationship develops (Biehal, 2014; Sen and Broadhurst, 2011).…”
Section: Introductionmentioning
confidence: 99%